Conservation agriculture for efficient resource use, sustainable crop production and better environment - Das, T K; Ghosh, Sourav; Datta, Debarati; Sen, Suman; Roy, Arkaprava; Raj, Rishi; Behera, Biswaranjan; Sharma, A R (Indian Farming, 2021)
Conventional agriculture characterized by repetitive tillage, residue removal/burning and monocropping is responsible for a plethora of problems including yield stagnation, degradation of soil and water quality, and environmental pollution. Conservation agriculture, a paradigm shift from conventional farming brings sustainability to the production system with enhanced crop yields, reduced production costs, higher resource (nutrient, water, energy) use efficiency, and improved soil and environmental quality. Success of a conservation agriculture system relies upon implementation of all three basic principles, viz. zero tillage, residue retention and crop rotation in efficient and holistic manner.